2003
DOI: 10.1614/0043-1745(2003)051[0013:atamof]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, translocation, and metabolism of foliar-applied CGA-362622 in purple and yellow nutsedge (Cyperus rotundus and C. esculentus)

Abstract: Studies were conducted to evaluate the absorption, translocation, and metabolism of 14C–CGA-362622 when foliar-applied to purple and yellow nutsedge. Less than 53% of the herbicide was absorbed after 96 h. Both nutsedge species translocated appreciable amounts of herbicide (30%) out of treated leaves. Translocation was both acropetal and basipetal, with at least 25% transported basipetally. Neither nutsedge species translocated more than 4% of applied radioactivity to the tubers and roots. Most of the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 30 publications
3
48
0
1
Order By: Relevance
“…Leys and Slife (1988) reported 58% of applied 14 C metsulfuron was readily absorbed by wild garlic (Allium vineale L.) 144 h after application and 16% of that absorbed material translocated out of the treated leaf. Troxler et al (2003) observed 53% or less of applied 14 C-trifloxysulfuron was absorbed by yellow nutsedge (Cyperus esculentus L.) and purple nutsedge (C. rotundus L.) 96 h after treatment. Unlike turfgrass, the least yellow nutsedge control was observed in Ultima (75 g haG 1 ) followed by Total (40 g LG 1 ) at all application (Table 3).…”
Section: Resultsmentioning
confidence: 93%
“…Leys and Slife (1988) reported 58% of applied 14 C metsulfuron was readily absorbed by wild garlic (Allium vineale L.) 144 h after application and 16% of that absorbed material translocated out of the treated leaf. Troxler et al (2003) observed 53% or less of applied 14 C-trifloxysulfuron was absorbed by yellow nutsedge (Cyperus esculentus L.) and purple nutsedge (C. rotundus L.) 96 h after treatment. Unlike turfgrass, the least yellow nutsedge control was observed in Ultima (75 g haG 1 ) followed by Total (40 g LG 1 ) at all application (Table 3).…”
Section: Resultsmentioning
confidence: 93%
“…Imazapic applications were timed to determine whether the physiological characteristics of deeproot sedge during the growing season would respond to herbicide application. Unless deeproot sedge was physiologically ready to translocate foliar-applied herbicide to the roots, only a top-kill would be expected (Brady and Hall 1976;King et al 2014;Sosebee 1984;Troxler et al 2003). Therefore, the most favorable control rates and timing for the herbicide application should be correlated with different stages of plant growth and carbohydrate storage.…”
Section: Resultsmentioning
confidence: 99%
“…Trifloxysulfuron (experimental code CGA-362622) is a new sulfonylurea herbicide recently registered for POST weed control in cotton (Gossypium hirsutum L.) (Burke and Wilcut 2004;Porterfield et al 2002a;Richardson et al 2003;Troxler et al 2003). Tolerance is based on rapid metabolism in tolerant species (Askew and Wilcut 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrithiobac and trifloxysulfuron are the only options for POST over-the-top tank mixtures for selective annual broadleaf weed control in transgenic herbicide-resistant cotton cultivars, including glufosinate-, glyphosate-, and bromoxynil-resistant cultivars Richardson et al 2003). Trifloxysulfuron also controls a number of perennial sedge species (McElroy et al 2003(McElroy et al , 2004Troxler et al 2003).…”
Section: Introductionmentioning
confidence: 99%